إستراتيجية مواجهة الضغوط النفسية وعلاقتها بالتحصيل الدراسي لدى التلاميذ المتفوقين دراسيا - بن عيسى, عبدالحكيم; زواري أحمد, خليفة (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة الحالية إلى التعرف على طبيعة العلاقة بين استراتيجيات مواجهة الضغوط النفسية والتحصيل الدراسي لدى التلاميذ المتفوقين دراسيا من السنة أولى ثانوي، حيث تم اختيار عينة الدراسة بالطريقة العشوائية الممثلة للنسب المتساوية في اختيار عينة الدراسة التي تتكون من تلاميذ المتفوقين دراسيا من السنة أولى ثانوي، والتي بلغ عددها ب(66) تلميذ وتلميذة من بينهم (21) ذكر و(45) إناث، وتم تطبيق المنهج الوصفي التحليلي ودراسة حالة لتحليل محتوى المقابلة بالإضافة إلى مقياس إستراتيجية مواجهة الضغوط النفسية من إعداد ومن أهم النتائج المتحصل عليها هي: - لا توجد علاقة ارتباطيه دالة إحصائيا بين إستراتيجية مواجهة الضغوط النفسية والتحصيل الدراسي لدى التلاميذ المتفوقين دراسيا. - لا يوجد فرق دال إحصائيا بين الذكور والإناث في إستراتيجية مواجهة الضغوط النفسية عند التلاميذ المتفوقين دراسيا. Abstract: The present study aimed to identify the nature of the relationship between strategies for facing psychological stress and academic achievement among students who have excelled in studies from the first year of secondary school, Where the study sample was chosen randomly, representing equal proportions in choosing the study sample, which consists of students who have excelled in studies from the first year of secondary school, Where the number of the sample was (66) male and female students, including (21) males and (45) females, The descriptive analytical approach and a case study were applied to analyze the content of the interview in addition to the Psychometric Stress Management Strategy Scale (Erickson, 1999), Among the most important results obtained are: - There is no statistically significant correlation between the strategy of facing psychological stress and the academic achievement of the students who have excelled in studies. - There is no statistically significant difference between males and females in the strategy of facing psychological pressures among students who have excelled in studies.
مقال
Keywords: الضغوط النفسية ; المواجهة; Psychological stress ; confrontation